2020
DOI: 10.1038/s41591-020-1008-z
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of TP53 allelic state for genome stability, clinical presentation and outcomes in myelodysplastic syndromes

Abstract: Tumor protein p53 (TP53) is the most frequently mutated gene in cancer 1,2. In patients with myelodysplastic syndromes (MDS), TP53 mutations are associated with high-risk disease 3,4 , rapid transformation to acute myeloid leukemia (AML) 5 , resistance to conventional therapies 6-8 and dismal outcomes 9. Consistent with the tumor-suppressive role of TP53, patients harbor both mono-and biallelic mutations 10. However, the biological and clinical implications of TP53 allelic state have not been fully investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
412
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 453 publications
(444 citation statements)
references
References 50 publications
25
412
7
Order By: Relevance
“…TP53 loss-of-function is a crucial event in the activation of mechanisms underlying tumor progression 8 . In order to identify CNVs in TP53 gene, we analyzed this region by MLPA in bulk CD34+ cells of T2 and T3, because of the significant expansion of the clones carrying TP53 p.Cys238Ser mutation in these timepoints.…”
Section: Single Cell Sequencing Allows the Characterization Of A Novementioning
confidence: 99%
See 1 more Smart Citation
“…TP53 loss-of-function is a crucial event in the activation of mechanisms underlying tumor progression 8 . In order to identify CNVs in TP53 gene, we analyzed this region by MLPA in bulk CD34+ cells of T2 and T3, because of the significant expansion of the clones carrying TP53 p.Cys238Ser mutation in these timepoints.…”
Section: Single Cell Sequencing Allows the Characterization Of A Novementioning
confidence: 99%
“…Since a recent work by Bernard et al demonstrated that TP53 impairment determines CNVs which correlate with poor prognosis in hematological malignancies8 , we deeply analyzed TP53 mutational state and identified a novel deletion at single cell level. Although this variant affects a small cell subpopulation, it could support the genomic instability that characterizes the accelerated phase of the disease.…”
mentioning
confidence: 99%
“…Deeper sequencing of CHIP mutations within TP53-mutated samples demonstrated sub-clonal chromosome 5 and 7 copy number variations many years before the diagnosis of t-MN, suggesting that TP53 clones precede the development of cytogenetic abnormalities in t-MN. Moreover, TP53 clones expand over time and drive transformation to t-MN, being the bulk of the malignant clone at diagnosis [61]. This intrinsic advantage may be related to a specific TP53-related immune escape phenotype, as shown by a recent study where TP53 mutant cases showed an imbalance of checkpoint molecules and expansion of highly immunosuppressive regulatory T cells and myeloid-derived suppressor cells [62] (Figure 2).…”
Section: The Case Of Tp53 and Ppm1d In Therapy-related Chipmentioning
confidence: 93%
“…Remarkably, TP53 mutations have the worst prognosis in MDS, including in patients who underwent HSC transplantation [82] and are linked to an increased risk of leukemic transformation [27]. A recent study from the International Working Group for Prognosis of MDS analyzed a large cohort (n = 3324) of de novo MDS and related myeloid neoplasms [105]. A comprehensive collection of cytogenetic data (G-banding analysis) and sequencing data (genome-wide copy number probes and capture-based NGS) were employed to resolve the clinical implications of TP53 mutations and their allelic status in MDS.…”
Section: Dna Transcription (Runx1 Tp53)mentioning
confidence: 99%